Development of low cost skinless pork longanisa - Del Mundo, Cheryl Ann V.
Optimizing the level of isolated soy protein and iota carrageenan produced a low cost skinless pork longanisa. All combinations of the upper and lower limits of iota carrageenan (0.5-0.2%) and isolated soy protein (3.5-2%) were incorporated to produce nine formulations including 0% of both for control and were subjected to physical and sensory analysis. In all the formulations tested, the 3.5% isolated soy protein and 0.2% iota carrageenan combination had the best results in terms of sensory attributes, cooking yield, water-holding capacity, and least shrinkage. Thus, it was chosen as the optimum level. The cost analysis showed that for every kilogram of the cooked skinless pork longanisa, a savings of P12.13 can be achieved and as much as P606.50 for 50 kilograms produced can be saved. The consumers' acceptability test result showed that the developed product was highly acceptable in terms of quality and price.